The action of secretin and pancreozymin on small-intestinal alkaline phosphatase. Issue 1 (January 1974) - Warnes, T. W.; Hine, P.; Kay, G.
Abstract : The hormones secretin and cholecystokinin-pancreozymin (CCK) have been shown to release brush-border alkaline phosphatase into the small-intestinal lumen in the human subject. In contrast to the disaccharidases, large amounts of alkaline phosphatase are present in human duodenal juice. The range has been established in normal subjects. Following the intravenous administration of both secretin and CCK-pancreozymin there is a large rise in the output of alkaline phosphatase in human duodenal juice. These rises are also present in patients with complete obstruction of the common bile and pancreatic ducts, and since the pancreatic juice of man contains negligible amounts of alkaline phosphatase, it is clear that both hormones must cause small-intestinal alkaline phosphatase to be released into duodenal juice. The isoenzyme characteristics of bile, small-intestinal, and pancreatic alkaline phosphatase have been established, and isoenzyme studies used to confirm this new action of secretin and CCK-pancreozymin.